Symbolic Representation of Young Children in Science: Insights into Preschoolers' Drawings of Change of State of Matter - Maria Kampeza; Alice Delserieys Pedregosa (MDPI AG, 2024)
Research in early childhood education acknowledges the multimodal nature of learning, and the need to equip young learners with the abilities to encounter future communication and learning challenges is imperative. Drawing can play a crucial role in children's learning in general and contribute to science learning in particular. In this paper, we study the drawings that young children (aged 4-6) produce during a teaching intervention about the change of state of matter. The research adopts a sociocultural perspective, considering drawing as a mediating tool to support children's meaning-making and learning process. The objective is to understand better the type of drawing situations that can be proposed to young children in science and the scaffold these drawing tasks might provide to support meaning-making in science. Results show that children use iconic as well as symbolic modes of representation depending on the situation and that the resources available can have an impact on how children use different symbols.